2007
DOI: 10.1111/j.1398-9995.2007.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergen‐induced in vitro expression of IL‐18, SLAM and GATA‐3 mRNA in PBMC during sublingual immunotherapy

Abstract: During SLIT, IL-18 and SLAM are upregulated, suggesting that the Th2 type inflammatory response is downregulated during SLIT by increased Th1 type response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 36 publications
2
34
0
1
Order By: Relevance
“…Moreover, a very recent study indirectly supports the relevance of the Th2-Thl shift as SLIT increases the expression of both IL-18 and SLAM (20). IL-18 is a macrophage-derived cytokine originally found as a factor inducing IFN-y production from Thl cells (26).…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, a very recent study indirectly supports the relevance of the Th2-Thl shift as SLIT increases the expression of both IL-18 and SLAM (20). IL-18 is a macrophage-derived cytokine originally found as a factor inducing IFN-y production from Thl cells (26).…”
Section: Discussionmentioning
confidence: 86%
“…120,121 Other studies of SLIT observed a suppression of T cells proliferative responses, elevated level of INF-gamma and a reduction in Th2 cytokines [122][123][124][125][126] whereas some studies did not confirm this last finding in peripheral blood cells. [127][128][129] Other immunological changes in peripheral blood mononuclear cells from SLIT treated patients include increased expression of the programmed cell death ligand (PD-L1) on B cells and monocytes. 130 A significant reduction in the number of eosinophils and neutrophils in the nasal mucosa 131 has been reported.…”
Section: Sublingual Immunotherapymentioning
confidence: 99%
“…Moreover, eosinophils are the main player, with activated T cells, of the late-phase reaction elicited by exposure to the specific allergen, leading to the initial release by mast cells of products with chemotactic activity, that represents a clinical model of allergic inflammation. The capacity of IT to suppress the late-phase reaction is well known for SCIT (19), and has recently been confirmed for SLIT (33). It was demonstrated that SLIT prevents the recruitment of eosinophils in the eye or in the nose following allergen challenge, decreases local or systemic levels of eosinophil cationic protein (45), and rapidly reduces (following a rush protocol) the recruitment of eosinophils -as well as neutrophils -into the nasal mucosa, along with the decreased expression of the ICAMI adhesion molecule (46).…”
Section: Effects On Mast Cells and Eosinophilsmentioning
confidence: 84%
“…The cytokine most recently investigated in IT is IL-18, originally found as a factor inducing IFN-gamma production from Th1 cells (32). In vitro studies have found that IL-18 in presence of1L-12 induces IFNgamma production and inhibits IgE synthesis and antigen-specific Th2 cell development, whereas in the absence of IL-12, IL-18 rather stimulate mast cells and basophils to produce IL-4 and IL-13, resulting in increased IgE synthesis (33) concerns the quick production of IFN-gamma, which was detected as soon as three months after the initiation of SLIT (34).…”
Section: Effects On T Cells and Cytokinesmentioning
confidence: 99%